Brand Image, Service Quality, and Customer Loyalty: Evidence From A Private-Owned Pharmacy with Physician Practice Services - Natalia Christiani Putri; Adryan Fristiohady; Ruslin Ruslin; Wahyuni Wahyuni; Suryani Suryani; Nur Illiyyin Akib (Indonesian Journal of Global Health Research, 2026)
Customer loyalty is a vital factor influencing sustainability and competitiveness in the pharmaceutical industry. Loyalty is determined by the quality of services provided and the robustness of the pharmacy's brand image. This research investigates the impact of brand image and service quality on customer loyalty at MM Pharmacy. A quantitative research design was employed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), with data gathered via surveys from 100 respondents selected through purposive sampling based on the Slovin formula. The findings indicate that brand image and service quality substantially influence consumer loyalty, with brand image exerting a more pronounced effect. Effect size analysis (f²) revealed that brand image exerted a substantial influence on customer loyalty (f² = 0.376), while service quality exhibited a minimal effect (f² = 0.130). This study also indicates that the R² value of 0.737 demonstrates that the joint impact of brand image and service quality explains 73.7% of the variance in customer loyalty, signifying a significant impact. The remaining 26.3% may be affected by additional variables not incorporated in the model. Furthermore, the Q² value, which evaluates predictive relevance, confirms the model's capability to accurately predict unobserved data by considering both exogenous and endogenous variables.